Dysregulation of Immunity in Pulmonary Fibrosis is Associated with Increased Myeloid-specific Triggering Receptor-1 and Transforming Growth Factor-beta1 Expression - Shima Rasouli; Jalal Heshmatnia; Nariman Mosaffa; Majid Marjani; Esmaeil Mortaz (Iranian Journal of Allergy, Asthma and Immunology, 2023)
Fibrosing pneumonia (FP) is classified into usual interstitial pneumonia (UIP) and nonspecific interstitial pneumonia (NSIP), each having its own etiology and prognosis. Both types of FP are progressive and chronic conditions with distinct etiologies. Cytokines and inflammatory mediators play critical roles in the pathogenesis of FP. Among them, the role of transforming growth factor beta-1 (TGF-β1) and modulators triggering fibrosis are not well understood. In this study, the expression of triggering receptor expressed on myeloid cells-1 (TREM-1) as a stimulator for the production of TGF-β1 and also CD4+CD25+Foxp3+ regulatory cells were investigted in FP patients. Sixteen UIP, 14 NSIP and 4 pulmonary fibrosis following Mycobacterium tuberculosis (TB) infection patients, were compared with 12 healthy controls. The frequency of blood CD14+TGF-β1+ and CD14+TREM1+-gated monocytes and CD4+CD25+Foxp3+ regulatory T cells (Treg), as well as the plasma levels of TGF-β1 and IL‑10 were measured. Fibrosis patients compared to healthy controls had a greater frequency of CD14+TGF-β1+ [15.9 (0.2-88.2) vs. 0.6 (0.2-11.0)] and CD14+TREM1+ [21.1 (2.3-91.2) vs. 10.3 (3.1-28.6)]-gated monocytes, and CD4+CD25+Foxp3+ [1.2 (0.3-3.6) vs. 0.2 (0.1-0.4)]-gated lymphocytes. Plasma TGF-β1 were also significantly increased in patients with fibrosis compared to healthy controls [9316.2 (±5554.4) vs. 3787.5 (±2255.6)]. These results confirm the importance of TGF-β1 and TREM1 in pulmonary fibrosis. It seems that this reciprocal cycle in healthy people is modulated by the production of IL‑10 by Treg cells, thus limiting fibrosis, as observed in patients following TB infection. Further investigations are recommended to evaluate possible immunomodulatory mechanisms defects in pulmonary fibrosis.